Effect of aerobic exercise on certain blood parameters of patients with type 2 diabetes - Yildirim, Zeynep; Bozkus, Taner (Progress in Nutrition, 2020)
Study Objectives:The objective of our study was to determine whether aerobic exercise has any effects on the thyroid hormone levels and certain blood parameters of patients with Type 2 diabetes. Methods:8 female patients with type 2 diabetes, whose average age was 39.62±6.30, years were voluntarily included inour study. Specialists obtained fasting blood samples from participants, who underwent an exercise programwith aerobic content, in a suitable laboratory environment in the predetermined health care institution in themorning in order to determine FT3, FT4, Triglyceride, Total Cholesterol, HDL, LDL, Iron, and B12 valuesbefore and after doing exercise. The case analysis method, which is one of the scientific research techniques,was used in the research, and pre- and post-test modelling were performed. Wilcoxon Signed Rank Test wasperformed in order to compare pre- and post-exercise values, and thus, analysis of obtained data was madeby descriptive statistics via SPSS 22.0 package program. Results: it was determined that the exercise programensured a statistically significant decrease to occur on the Weight, BMI, Total Cholesterol, TRIG, HDL,LDL, T3, and T4 values of sedentary patients and women with type 2 diabetes (p0,05). Blood and weight values, whichwere are-obtained done a week from tests made in the previous week, were similar to post-test measurements. Conclusion:We may say that, in this research that is conducted on female patients with type 2 diabetes,8 weeks of aerobic exercise made a positive effect on organizing thyroid hormone, as well as weight loss andblood lipids. Furthermore, we are of the opinion that type 2 diabetic syndrome, which is caused by a sedentary lifestyle and irregular eating habits, may be adjusted by regular and long-term exercise program and byreinforcing insulin resistance.